Assessment of Arteriovenous Shunt Pathway Function and Hypervolemia for Hemodialysis Patients by Using Integrated Rapid Screening System - Chen, Wei-Ling; Lin, Chia-Hung; Kan, Chung-Dann (Advances in Technology Innovation, 2017)
Currently, the hemodialysis patients received body weight measurement by themselves, vital sign checking by nursing staffs before dialysis. Whenever, the arteriovenous routes with problems doubted, the patients needed to be referred to surgeon for vascular echography checking and then to be corrected. How to integrate these three tasks in one time is a very important issue. The project proposes to combine our previous study of audio-phono angiographic technology in detecting vascular stenosis with rapid screening system to evaluate dialysis patients’ arteriovenous routes function and their status of excess body fluids: inspecting and integrating the blood pressure, body weight, and fistula function work into a rapid screening system, and using the quantization of fistula phono angiography pitch to achieve assessing arteriovenous routes. Future hoping is developed a complete integrated intelligence system by combining the arteriovenous fistula signal processing with feature extraction with wireless sensor network technology.